Business Process Reengineering pada CV. Pustaka Grafika Malang - Rayhan Putra Fajar; Ilyas Nuryasin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
CV. Pustaka Grafika is a book printing company that serves both individual and educational institution orders. The company's supervision and production processes are currently conducted manually. This often results in unavoidable waiting times for each team. This research aims to enhance operational efficiency at CV. Pustaka Grafika by applying the Business Process Reengineering (BPR) methodology. The pre-existing business processes were analyzed for their efficiency through a throughput efficiency test. A recommended business process was then developed based on the previous process and subjected to a throughput efficiency test. This BPR research resulted in a throughput efficiency of 93.9%, compared to the previous 49.46%. The recommended business process demonstrated a 44.44% improvement over the initial process. By leveraging advancements in technology and information, a website can be utilized to support the digitalization and automation of the recommended business processes at CV. Pustaka Grafika. This study is limited to UI/UX design recommendations using Figma and a limited evaluation of the design's performance, excluding technical implementation or extensive user testing.